71 Up-titration of secondary prevention following acute coronary syndrome (acs). (5th June 2017) - Fhadil, Sadeer; Timmis, Adam; Ruparelia, Niket; Wright, Paul; Patel, Riyaz; Sud, Preeti; Robson, John; Antoniou, Sotiris
Abstract : Introduction: Optimum doses of secondary prevention cardiac medicines need to be achieved post-ACS to derive evidence-based benefits, including reductions in mortality, hospital readmission and improved symptom control. High intensity statin therapy can be started immediately at high-target dose, whilst ACE inhibitors (ACEi) and beta-blockers require up-titration to reach maximum tolerated doses. Despite a high percentage of patients being discharged on appropriate secondary prevention post-ACS, doses of ACEi and beta-blockers at the point of discharge are not at target dose due to haemodynamic effects and require up-titration post discharge. The aim of this study is to assess doses of ACEi and beta-blockers at the point of discharge and at various time points following discharge to assess rates of up-titration. Method: Patients discharged following ACS in September 2015, April 2016, July 2016 and September 2016 were identified using the Myocardial Ischemia National Audit Project (MINAP). Using electronic patient records, discharge doses of ACEi (or ARBs), beta blockers and statins were recorded. Patients were contacted in October 2016 to assess current doses of ACEi (or ARBs), beta blockers and statins corresponding to rates of up-titration at 1, 3, 6 and 12 months post-ACS. Full dose equivalents (FDE) were used to standardise variability of dosing between different ACEi (or ARBs), beta blockers and statins. FDE ranged from 0, those not on the class of medication, to 1, those on maximum doses. Patients without a true diagnosis of ACS or those deceased were excluded from the study. Results: 635 patients were identified from MINAP, of which 349 met the inclusion criteria for analysis. Baseline characteristics were similar between groups. Up-titration occurred in 53 patients (15%) taking beta blockers and 79 patients (23%) taking ACEi (or ARBs); however optimal doses of beta blockers and ACEi (or ARBs) were only achieved in 32 patients (9%) and 40 patients (11%) respectively. Average FDE of beta blockers and ACEi (or ARBs) was 0.38 and 0.37 respectively. 270 patients (77%) were taking optimal doses of statins, with an average FDE of 0.86. No differences were seen with regards to up-titration of secondary prevention at different time points. Conclusions: Results demonstrate an opportunity to titrate doses of beta blockers and ACEi (or ARBs) to optimal doses following ACS. NICE suggests up-titration to maximum doses within 4–6 weeks of discharge; however, whilst there is a positive trend in the number of patients on optimum doses with time, up-titration is minimal with patients achieving one third of target doses up to one year post-ACS. Data from this study shows a growing need to support patients in the community to optimise cardiac medications for secondary prevention after an ACS.